Association of the Female Athlete Triad Risk Assessment Stratification to the Development of Bone Stress Injuries in Collegiate Athletes. (February 2017) - Tenforde, Adam S.; Carlson, Jennifer L.; Chang, Audrey; Sainani, Kristin L.; Shultz, Rebecca; Kim, Jae Hyung; Cutti, Phil; Golden, Neville H.; Fredericson, Michael
Background: The female athlete triad (referred to as the triad) contributes to adverse health outcomes, including bone stress injuries (BSIs), in female athletes. Guidelines were published in 2014 for clinical management of athletes affected by the triad. Purpose: This study aimed to (1) classify athletes from a collegiate population of 16 sports into low-, moderate-, and high-risk categories using the Female Athlete Triad Cumulative Risk Assessment score and (2) evaluate the predictive value of the risk categories for subsequent BSIs. Study Design: Cohort study; Level of evidence, 3. Methods: A total of 323 athletes completed both electronic preparticipation physical examination and dual-energy x-ray absorptiometry scans. Of these, 239 athletes with known oligomenorrhea/amenorrhea status were assigned to a low-, moderate-, or high-risk category. Chart review was used to identify athletes who sustained a subsequent BSI during collegiate sports participation; the injury required a physician diagnosis and imaging confirmation. Results: Of 239 athletes, 61 (25.5%) were classified into moderate-risk and 9 (3.8%) into high-risk categories. Sports with the highest proportion of athletes assigned to the moderate- and high-risk categories included gymnastics (56.3%), lacrosse (50%), cross-country (48.9%), swimming/diving (42.9%), sailing (33%), and volleyball (33%). Twenty-five athletes (10.5%) assigned to risk categories sustained ≥1 BSI. Cross-country runners contributed the majority of BSIs (16; 64%). After adjusting for age and participation in cross-country, we found that moderate-risk athletes were twice as likely as low-risk athletes to sustain a BSI (risk ratio [RR], 2.6; 95% confidence interval [95% CI], 1.3-5.5) and high-risk athletes were nearly 4 times as likely (RR, 3.8; 95% CI, 1.8-8.0). When examining the 6 individual components of the triad risk assessment score, both the oligomenorrhea/amenorrhea score ( P = .0069) and the prior stress fracture/reaction score ( P = .0315) were identified as independent predictors for subsequent BSIs (after adjusting for cross-country participation and age). Conclusion: Using published guidelines, 29% of female collegiate athletes in this study were classified into moderate- or high-risk categories using the Female Athlete Triad Cumulative Risk Assessment Score. Moderate- and high-risk athletes were more likely to subsequently sustain a BSI; most BSIs were sustained by cross-country runners.